Development of Historical Melodies to Build Character Profile of Pancasila Students - Idrus; Lukman Nadjamuddin; Junarti (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This research aims to develop Historical Dialogue Sheet (Melody) Media to build the character of the Pancasila Student Profile. The duration of the research is 12 months using the Research and Development method with stages; (1) introduction, (2) development, (3) and evaluation. The products developed consist of; Historical Melody Scenarios, Historical Melody Imaginative Discourse, and Historical Melody Matrix. The trials were carried out three times, namely limited trials, large group trials and main product trials. Increasing the character of the Pancasila Student Profile in the class in the dimensions; (1) Have faith and devotion to God Almighty and have noble character; (2) Global Diversity; (3) Independent; (4) Working together; (5) Creative; (6) Critical, in limited trials qualitatively categorized as quite good (70.83%). Meanwhile in the large group trial it was categorized as good (83.33%), while in the main product trial it was categorized as very good (91.66%). Improving the character of the Pancasila Student Profile outside the classroom, discipline indicators, following the flag ceremony in limited group trials is categorized as Mulia Visible (MT), large group trials and main product trials are categorized as Starting to Develop (MK). For indicators of respecting the red and white flag during ceremonies in limited group trials, they are categorized as Starting to Be Seen (MT), large group trials and main products are categorized as Starting to Develop (MK). The indicator of singing the song Indonesia Raya with enthusiasm in limited group trials is categorized as Starting to Become Visible (MT), in large group trials is categorized as Starting to Develop (MK) and in main product trials it is categorized as Starting to Develop (MB). Indicators of disposing of waste in the places provided in limited group trials are categorized as Starting to Develop (MK) and large group trials and the main product are categorized as Starting to Develop (MB). The indicator of wanting to get along and help each other between religious communities at all levels of the trial is categorized as Starting to Develop (MK).